Engineering Problem Solving with Matlab / Second Edition - Etter Delores M (Prentice Hall International, 1997)
Fundamental Engineering Computing, Engineering Problem Solving, MATLAB Environment, MATLAB Functions, Linear Algebra and Matrices, Numerical Techniques, Solutions to Systems of Linear Equations, Interpolation and Curve Fitting, Numerical Integration and Differentiation, Ordinary Differential Equations, Special Topics, Symbolic Mathem,atics, Sigmal Processing, Control Systems, Appendix A: MATLAB Function Summary, Complete Solutions to Practice Problems, Index.